2011
DOI: 10.3389/fnana.2011.00005
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Development of Thick-Tufted Layer V Pyramidal Cells in the Rat Somatosensory Cortex

Abstract: The thick-tufted layer V pyramidal (TTL5) neuron is a key neuron providing output from the neocortex. Although it has been extensively studied, principles governing its dendritic and axonal arborization during development are still not fully quantified. Using 3-D model neurons reconstructed from biocytin-labeled cells in the rat somatosensory cortex, this study provides a detailed morphological analysis of TTL5 cells at postnatal day (P) 7, 14, 21, 36, and 60. Three developmental periods were revealed, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
106
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 107 publications
17
106
0
Order By: Relevance
“…Table 3 summarizes key morphological properties of these cells. The statistics of this dataset matched the experimental statistics reported previously (Romand et al 2011), and thus indicated that the set of morphologies faithfully represents the TTC population in young Wistar rats. We note that the difference in surface area between morphologies was not only due to differences in total dendrite length, but also to differences in dendritic diameter.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Table 3 summarizes key morphological properties of these cells. The statistics of this dataset matched the experimental statistics reported previously (Romand et al 2011), and thus indicated that the set of morphologies faithfully represents the TTC population in young Wistar rats. We note that the difference in surface area between morphologies was not only due to differences in total dendrite length, but also to differences in dendritic diameter.…”
Section: Resultssupporting
confidence: 63%
“…Layer 5 thicktufted pyramidal cells (TTCs) are characterized by prototypical morphological features and can also be classified as an e-class, differing even from their neighboring L5 thintufted pyramidal cells in spike threshold, amplitude, halfwidth, and initial burst interspike interval (ISI) (Le ). Nevertheless, although TTCs have unique morphological characteristics, they vary widely in their dendritic length, surface area, and the complexity of their branching pattern (Le Be et al 2007;Romand et al 2011;Zhu 2000). A significant portion of the ionic current entering the axon via its membrane ion channels leaks axially into the soma and dendrites; similarly, currents entering the soma via its membrane ion channels leak primarily into the dendrites (Rall 1959).…”
mentioning
confidence: 99%
“…We observed unedited GluA2(Q) transcripts in vivo and in OTC up until the first postnatal day, suggesting that some calciumpermeable GluA2 protein might well be present during the time when dendritic trees enlarge and synapses form by mechanisms not yet driven by sensory input (Romand et al, 2011). The immature brain employs unedited GluA2(Q) in addition to GluA2(R) to mediate the trophic actions of glutamate (Burnashev et al, 1992).…”
Section: The Importance Of Flip and (Q) Variantsmentioning
confidence: 96%
“…Development 138 (19) independent phase of growth (Romand et al, 2011). However, basal dendrites at this age are growth competent and respond, for instance, to TrkB ligands .…”
Section: Research Articlementioning
confidence: 99%
“…This may suggest that cell type is important for determining both rapid estrogenic effects and the underlying molecular mechanisms and that there are compartment-specific (i.e., apical versus basal dendrites) 17b-estradiol signaling mechanisms. Such a scenario is not unprecedented because differential mechanisms have been described for the development and maintenance of apical and basal architecture (Romand et al, 2011;Srivastava et al, 2012c). If distinct regions of the dendritic tree contain specific molecular mechanisms that control dendritic arborization, it is plausible that a similar subcompartmental specialization may exist for the regulation of synapse structure.…”
Section: Molecular Mechanisms Of Dendritic Spine Remodeling In Hipmentioning
confidence: 99%